2015
DOI: 10.18632/oncotarget.4198
|View full text |Cite
|
Sign up to set email alerts
|

MIF, secreted by human hepatic sinusoidal endothelial cells, promotes chemotaxis and outgrowth of colorectal cancer in liver prometastasis

Abstract: Growth and invasion of metastatic colorectal cancer (CRC) cells in the liver depend on microenvironment. Here, we showed that human hepatic sinusoidal endothelial cells (HHSECs) induce chemotaxis and outgrowth of CRC cells. Macrophage migration inhibitory factor (MIF), released by HHSECs, stimulated chemotaxis of CRC cells. MIF secreted by HHSECs, but not by CRC cells themselves, promoted migration and epithelial-mesenchymal transition (EMT) and facilitated proliferation and apoptotic resistance of CRC cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 50 publications
1
42
0
Order By: Relevance
“…Our findings are consistent with recent evidence suggesting the potential value of cofilin in the context of the actin cytoskeleton in the development of prostate cancer and lymph node metastasis [34]. Phosphorylation of cofilin in colorectal cancer cells caused by migration inhibitory factor accelerated mobility of cancer cells toward an invasive and metastatic phenotype [35]. Moreover, our results demonstrate a significant association between EMT and increased nuclear cofilin levels and bladder cancer–related death.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with recent evidence suggesting the potential value of cofilin in the context of the actin cytoskeleton in the development of prostate cancer and lymph node metastasis [34]. Phosphorylation of cofilin in colorectal cancer cells caused by migration inhibitory factor accelerated mobility of cancer cells toward an invasive and metastatic phenotype [35]. Moreover, our results demonstrate a significant association between EMT and increased nuclear cofilin levels and bladder cancer–related death.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, bone marrow chimeric mice expressing WT bone marrow on a Mif−/− background were protected from ethanol-induced liver injury. While these studies cannot exclude a potential contribution of MIF in other hepatic cell types, such as endothelial cells[32] or hepatic stellate cells[33], they are consistent with a likely role of hepatocytes as an important cellular source of MIF in the liver.…”
Section: Discussionmentioning
confidence: 71%
“…Keshamouni et al found that MIF was up‐regulated during TGF‐β induced EMT via temporal quantitative proteomic analysis in lung adenocarcinoma cells. Hu et al validated that MIF could promote migration, proliferation, and EMT, and MIF facilitated colorectal cancer cells transfer to liver and the level of MIF was related to the size of hepatic metastases. Zeng et al noted that inhibition of MIF through siRNA could repress biological behavior of oral squamous cell carcinoma (OSCC) cells, and the level of Twist was decreased in the MIF‐knockdown OSCC cells, simultaneously.…”
Section: Discussionmentioning
confidence: 99%